Evaluasi Pembangunan Pelabuhan Pulau Dompak oleh Kantor Kesyahbandaran dan Otoritas Pelabuhan Kelas II Tanjungpinang - ENDRI SANOPAKA; NURBAITI USMAN SIAM; Theresia Loly Trionika (STISIPOL Raja Haji, 2021)
As one of the provinces with archipelagic characteristics, the development of ports in the Riau Islands Province (Kepri) is the focus of attention in supporting inter-island connectivity. Dompak Port is a port that was built through a budget from the central government at the suggestion of the Riau Islands provincial government. According to the hierarchy, the Dompak port is a regional feeder port and in future development plans it will become a collecting port according to the Tanjungpinang City Sea Port Master Plan (RIP), Riau Islands Province. Dompak Port will provide many benefits for the regional shipping flow of the Riau Islands Province in general. Since it was built in 2009 until the sixth phase (out of the seven planned stages), the Dompak port has not been operational and has even resulted in legal issues and was temporarily suspended. The purpose of this study was to evaluate and find the factors that caused the cessation of the implementation of the Dompak Island port development. This type of research is an evaluative research with a qualitative approach. Informants in this study were employees of the Port Authority Office and Class II Tanjungpinang Port Authority. The data used in this study are primary data and secondary data, with data collection techniques in the form of observation and interviews. Data analysis was carried out by qualitative analysis. The results of this study found that the construction of the Dompak Island port was not in accordance with what was planned by the government because this Dompak port should have been completed and operationalized in 2015. There are factors that become obstacles in the construction of the Dompak Island port which has been built by the Harbormaster Office and the Authority. Tanjungpinang Class II Port, the land grant belonging to the Riau Islands Province government has not yet been completed as the proposing party to the Directorate General of Sea Transportation of the Ministry of Transportation through the Office of Harbormaster and Class II Tanjungpinang Port Authority.